Gender, Victimization, and Commercial Sex: A Comparative Study - O'Doherty, Tamara; Waters, Ian (Atlantis, 2019)
This article critically examines and compares adult male and female experiences selling sex in Canada’s off-street sex industry. Findings indicate that gender disparities exist when it comes to the work of selling sex: male providers are better insulated from violence and exploitation because of their gender, while female sex workers are forced to navigate multiple layers of oppression to assure safer working conditions. Despite these differences, this data suggests that prioritizing overarching labour issues, instead of gendered experiences working in commercial sex, can function to increase all sex workers’ safety and access to justice.